A Comprehensive Approach to Enhancing Volleyball Skills: The Role of Problem-Based Learning, Constraint-Led Approach, and Motivation - Awaluddin, Awaluddin; Samsudin, Samsudin; Puspitorini, Wahyuningtyas; Widiastuti, Widiastuti; Syahruddin, Syahruddin (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to assess whether there is a difference in influence between Constraint-Based Problem-Solving (CBA-PBL) and PBL (Problem-Based Learning), whether there is an interaction between the PBL-CBA model and motivation, and whether there is a difference in influence between students who have high and low motivation after undergoing PBL-CBA and PBL models. Materials and methods. The study employed an experimental method with a 2 x 2 factorial design, where treatment was needed, involving 40 students. Results. The results of the study obtained the value of F count PBL-CBA (A1) and PBL (A2) = 105.144 (P < 0.05), thereby indicating a significant difference (µA1 = 106.6 > µA2 = 100.4). Fcount interaction PBL (A)*motivation (B) = 280.779 (P < 0.05), thus there is a substantial interaction. A comparison of µA1B1 and µA2B1 yielded a result of 23.5000*, [Sig. 0.000 < 0.05; CI 95% = 212.156 - 257.844]. A comparison of the effect of µA1B2 and µA2B2 is -3.9000*, [Sig. 0.000 < 0.05; CI 95% = -61.844 - -16.156], reinforced by homogeneous results from different sub-sets. Conclusions. The conclusion of this study is that PBL can be pushed further in the sense that learners enter into real problems, become part of the problem situation, and problems or constraints can be improved in terms of constellation. The findings suggest that there is an interaction between PBL and motivation, the existence of a problem in the form of a task generates motivation to solve it, and the problem is successfully solved when the learner has motivation. Learning with a constraint-led approach must be appropriate to the learner’s characteristics, any attempt to increase the task must be given and reviewed very wisely.